Realization of an auto-calibrated long-range VGA extender - Yuh-Chin Chang; Tsung-Mou Tsai; Shun-Pin Hsu; Huei-Jhan Lin (2011 6th IEEE Conference on Industrial Electronics and Applications, 2011)
In this paper we construct a long-distance VGA signal extending system featuring the self-tuning capability. The physical carrier of the signal is the typical local area network (LAN) cables such as CAT-5e. By investigating the noise distributions over the carrier a video restoration algorithm is proposed. The algorithm calculates the associated statistics and identifies the optimal IC control parameters for gain, equalization and color skews in the sense of the minimum errors or variance in certain color space. A 300-meter real-time image transmission example is given to demonstrate the effectiveness of the proposed approach.